2012
DOI: 10.1080/19439342.2011.641994
|View full text |Cite
|
Sign up to set email alerts
|

Targeting effectiveness of social cash transfer programmes in three African countries

Abstract: Social transfers are increasingly seen as a key tool in east and southern Africa for combating the triple threat of chronic poverty, hunger and HIV. In designing programmes, targeting has emerged as a contentious issue in the region. Compared with other regions, programmes in sub-Saharan Africa have been characterised by multiple targeting methodologies, including a substantial role of the community in identifying and prioritising beneficiaries. To help better understand some of the different targeting approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…To foster gradual independence from the program, households with an OVC over the age of 18 are no longer eligible. Impact evaluation results using the 2007 to 2011 data indicate that the program employed effective targeting (Handa et al 2012), increased human capital investment (The Kenya CT-OVC Evaluation Team 2012b), increased household consumption of food and non-food items (The Kenya CT-OVC Evaluation Team 2012a), thus meeting several important poverty-related targets.…”
Section: The Kenyan Cash Transfer For Orphans and Vulnerable Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…To foster gradual independence from the program, households with an OVC over the age of 18 are no longer eligible. Impact evaluation results using the 2007 to 2011 data indicate that the program employed effective targeting (Handa et al 2012), increased human capital investment (The Kenya CT-OVC Evaluation Team 2012b), increased household consumption of food and non-food items (The Kenya CT-OVC Evaluation Team 2012a), thus meeting several important poverty-related targets.…”
Section: The Kenyan Cash Transfer For Orphans and Vulnerable Childrenmentioning
confidence: 99%
“…Therefore, although the longitudinal data often include information on household and individual characteristics since the 2007 baseline, information on fertility is only available for one point in time in 2011. Further information on sample design is available elsewhere (Handa et al 2012; Handa et al 2014a). This study was approved by the Kenya Medical Research Institute Ethics Review Committee (Protocol #265) and the Institutional Review Board of the University of North Carolina.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…That program was replaced in 2005 by the Agricultural Input Subsidy Programme, in which eligible farmers received coupons that could be redeemed for fertilizer and seeds at heavily subsidized prices (Chirwa and Dorward, 2013). In 2006, the government also launched the Social Cash Transfer Program that provided ultra-poor and labour-constrained households with monthly cash payments (Handa et al, 2012). While these policies were implemented, Malawi occasionally experienced acute food shortages caused by bad weather.…”
Section: Context Of Rural Livelihood In Malawimentioning
confidence: 99%
“…The dependency ratio criterion was problematic because it failed to reach the poor with a low dependency ratio (exclusion error) and incorporated the non‐poor with a high dependency ratio (inclusion error). Despite generally acceptable targeting outcomes (Handa et al, ), the CT in Mozambique did not include a sufficient number of vulnerable children, was biased toward smaller households, and featured a number of unclear implementation rules, resulting in more arbitrary interpretation (Cunha et al, ). Regularity of payments: Only if people feel confident that they will receive cash on a regular basis will they make long‐term plans about consumption, saving, and investment (Lagarde, Haines, & Palmer, ). Irregularity in payment is a big problem in Ghana, where it was reported that the next transfer after the cash disbursement in May 2011 was 8 months later (Handa et al, ; UNICEF‐ESARO, ).…”
Section: Design and Implementation Featuresmentioning
confidence: 99%
“…In Kenya, on the other hand, payments to HSNP beneficiaries have been fairly regular (Oxford Policy Management and Institute of Development Studies, ). CT programs that have had a bigger impact on food security, primarily in Zambia (UNICEF‐ESARO, ) and Kenya (CT programs for OVC; Ward et al, ), are characterized by timely payments to beneficiaries. Transfer size: The monetary value of the transfer should be big enough to change the life of the beneficiaries, but not so big as to generate negative incentives to work and cause inequality and conflicts between those just below the eligibility threshold and those just above it (Handa et al, ). There is now some evidence about the necessary minimum threshold: 20 percent of the consumption of the poor.…”
Section: Design and Implementation Featuresmentioning
confidence: 99%